A Case-Based Critical Care Curriculum for Resident Physicians - Başak Çoruh; Patricia A. Kritek (Association of American Medical Colleges, 2012)
Abstract At our institution, medical and surgical intensive care unit (ICU) teams comprise an attending physician, fellow, nurse practitioner, and four to six resident physicians receiving training in anesthesiology, emergency medicine, family medicine, general surgery, or internal medicine. Resident physicians are encouraged to receive didactic instruction during their ICU rotations in addition to the bedside teaching that occurs during work rounds. Over the years, it became apparent that implementation of this instruction was inconsistent. This resource is a curriculum designed to address inefficiencies in our prior system and to provide consistency in resident education in critical care. The resource consist of an interactive, case-based framework to cover the core learning objectives for each topic in the curriculum. Each set of cases includes a patient scenario, a series of questions that can be posed to the residents, and an answer key. Teachers are encouraged to work through the cases systematically but have the flexibility to add material if they have additional expertise in the area. We also created a teaching calendar. Teaching occurs in the medical ICU before work rounds 4 days a week for 30 minutes per session. Twice weekly, the surgical ICU team attends didactics on core critical care topics. Each topic is covered once during the 4-week rotation in the ICU, and the calendar specifies the date upon which a topic is covered. We also left several open sessions to allow faculty and fellows the opportunity to provide instruction on topics outside the set curriculum. Faculty and fellows can access the curriculum materials via a secure electronic reserve. Faculty who may not have as much expertise in a given area now have a set of cases they can use to guide instruction in that area. ICU fellows also lead some of the teaching sessions, creating opportunities for trainees to receive feedback about their teaching.